Studi financial literacy, financial self-efficacy, financial behavior dosen Universidade da Paz Timor Leste - Leonardo Bele Bau Amaral; Rr Iramani; Tanza Dona Pertiwi (Universitas Hayam Wuruk Perbanas, 2024)
Financial behavior reflects how individuals manage financial resources to meet their needs and achieve life goals. Financial behavior, when supported by financial literacy, experience, and self-efficacy, can enhance living standards. This study aims to explore the influence of financial literacy, financial experience, and the role of financial self-efficacy as an intervening variable. of lecturers at Universidade da Paz. The sample was taken using purposive sampling. Total respondents were 100 lecturers at Universidade da Paz Timor Leste. Research on financial behavior has been conducted in Indonesia and other countries. However, similar research has not touched the society in Timor Leste. Therefore, this research is very important to do in order to enrich empirical findings in behavior finance research. Data was collected using the survey method through questionnaires. Analysis is conducted using SEM-PLS. The results showed that financial literacy and financial experience had no significant direct effect on financial behavior. Financial self-efficacy has a significant positive effect on financial behavior and is proven as a mediator in the relationship between financial experience and financial behavior. The implication is that Universidade da Paz lecturers should improve their financial experience by growing their self-efficacy which in turn makes their financial behavior better.